Tailoring Interfacial Oxygen Vacancy-Mediated Ordering in Ternary Pt3(Co,Mn)1 Intermetallic Nanoparticles for Enhanced Oxygen Reduction Reaction - Park, Yeji; Seok, Jun Ho; Park, Jae-Hyun; Kim, Doyeop; Cho, Seong Chan; Kim, Minsu; Jeong, Yujin; Kim, Taekyoung; Baik, Hionsuck; Lee, Sang Uck; Yoo, Sung Jong; Lee, Kwangyeol (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2026)
The sluggish kinetics and limited durability of the oxygen reduction reaction (ORR) at the cathode remain a major barrier to the widespread deployment of proton exchange membrane fuel cells (PEMFCs). Here, we introduce a low-temperature interfacial engineering strategy to construct ternary L12-ordered Pt3(Co,Mn)1 intermetallic nanoparticles. A conformal MnO shell on Pt3Co1 cores not only suppresses particle coalescence but also undergoes redox activation to generate interfacial oxygen vacancies that initiate the disorder-to-order transition. During thermal activation, these vacancies mediate Co-Mn atomic exchange across the core@shell interface, forming interfacial Co-O and intralattice Pt-Mn bonds that cooperatively stabilize the ordered framework. This oxygen-vacancy-driven interfacial evolution reconfigures the Pt electronic structure, downshifting the d-band center, enriching electron density at Pt active sites, and optimizing oxygen-intermediate adsorption. The resulting catalyst exhibits high intrinsic ORR activity and outstanding durability over extended accelerated cycling. When implemented into practical membrane-electrode assemblies, it surpasses the U.S. Department of Energy (DOE) 2025 PEMFC benchmarks for both rated power density and durability, demonstrating its promise for real-world fuel cell applications. More broadly, this work establishes redox-active, confinement-mediated interfacial engineering as a general paradigm for directing atomic ordering and electronic structure in complex multimetallic electrocatalysts.